Robotic-arm stereotactic radiosurgery as a definitive treatment for gelastic epilepsy associated with hypothalamic hamartoma - Susheela, Sridhar Papaiah (BMJ Publishing Group, 2013)
Gelastic seizures, characterised by paroxysms of pathological laughter, are most often associated with an underlying hypothalamic hamartoma. This report describes the definitive treatment using stereotactic-radiosurgery for a teenaged child whose gelastic epilepsy was found refractory to various antiepileptic drugs. Since surgery was not consented to, the child was referred to us for stereotactic radiosurgery (SRS), which was delivered with robotic-arm -SRS to a dose of 30 Gy in five fractions in five consecutive days. A decrease in the frequency of seizures was noticeable as early as within a week, and at 12 months after the procedure, there has been a total cessation of seizures.